Fostering Halal and Thoyyibah Food in Early Childhood Education - Wahju Dyah Laksmi Wardhani; Sawitri Komarayanti; Tri Endang Jatmikowati; Misyana Misyana (Universitas Muhammadiyah Mataram, 2018)
This study aims to construct the idea or thought regarding the importance of introducing halal and good food through early childhood education. Little children, including those of Muslims, generally do not have adequate knowledge about halal and good food according to Islamic jurisprudence (fiqh Islam). Children’s pattern of consumption, types of food they eat, and the ingredients of food cooked for them are generally determined by their parents or influenced by their social and cultural environments. By means of early childhood education, the knowledge of halal and good food is introduced earlier to the children in gradual steps in line with their age and developmental phases. Through constructivist-interpretive approach, this study is intended to analyze the importance of introducing, disseminating, and internalizing the knowledge, attitude, and skill about halal and good food to the children. The study also provides the children with graded lessons to identify halal and good food. The ultimate end the analysis is expected to yield integrated lessons on halal and good food within the curriculum of early childhood education.